Analyzing How Indonesian’s Mass Media Shaping Frame of Reference about Russian President (Vladimir Putin) - Sunata, Ivan; Khairul Nuzuli, Ahmad (Jurnal Dakwah dan Komunikasi, 2024)
In the last two years the war between Russia and Ukraine has attracted world attention. In Indonesia, the conflict between the two countries entered the public domain, causing society to split into two parts, namely supporters of Russia and supporters of Ukraine. In contrast to other international issues, such as Palestine, Uighur Muslims in China and so on, rejection of Russia's invasion of Ukraine is almost unheard of among Indonesian people. This is certainly very contradictory compared to the attitude of the Indonesian people towards other international issues. This article discusses the role of mass media in Indonesia in framing Russia, so that in the Russia-Ukraine conflict, many Indonesian people supported Russia. Based on observations of news from Indonesian online mass media such as Republika and others, this article argues that positive reporting on the figure of Russia's Vladimir Putin attracts Indonesian people's sympathy and support for Russia.